2023
DOI: 10.3389/fnhum.2022.1006350
|View full text |Cite
|
Sign up to set email alerts
|

Positive changes to written language following phonological treatment in logopenic variant primary progressive aphasia: Case report

Abstract: Phonological impairment contributes to deficits in repetition and spoken naming in logopenic variant Primary Progressive Aphasia (lvPPA), but weakened phonology can also affect written language skills. In this experimental case report, we demonstrate phonological text agraphia in a 71-year-old woman in the early stages of lvPPA that undermined her ability to write meaningful, grammatical sentences. We investigated the therapeutic value of a rigorous treatment protocol to strengthen phonological manipulation sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Additionally, the phonological treatment including sublexical letter-tosound mapping and phonological manipulation has not been paired with NIBS in PWA. In an individual with primary progressive aphasia, this treatment combined with anodal tDCS to the left IFG demonstrated significant generalization to written language production, including written narratives (Nickels et al, 2023).…”
Section: Current Evidence Of Tdcs Effects On Generalization and Funct...mentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the phonological treatment including sublexical letter-tosound mapping and phonological manipulation has not been paired with NIBS in PWA. In an individual with primary progressive aphasia, this treatment combined with anodal tDCS to the left IFG demonstrated significant generalization to written language production, including written narratives (Nickels et al, 2023).…”
Section: Current Evidence Of Tdcs Effects On Generalization and Funct...mentioning
confidence: 93%
“…Following this treatment sequence, PWA have shown improvement in transcoding and phonological manipulation skills (DeMarco et al, 2018). More importantly, several studies have demonstrated generalized gains to written language production, including reading and spelling of words and non-words as well as increased accuracy of written narratives (Nickels et al, 2023), with greater inclusion of morphological markers and functors.…”
Section: Attentionmentioning
confidence: 99%